Sensors and Instrumentation, Volume 5 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Wee Sit, Evro (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Sensors and Instrumentation, Volume 5. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the fifth volume of ten from the Conference brings together contributions to this important area of research and engineering. Th e collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Experimental Techniques • Smart Sensing • Rotational Eff ects • Dynamic Calibration • Systems & Sensing Technologies • Modal Transducers • Novel Excitation Methods.